Membrane-Interacting DNA Nanotubes Induce Cancer Cell Death - Samet Kocabey; Aslihan Ekim Kocabey; Roger Schneiter; Curzio Rüegg (Nanomaterials, 2021)
DNA nanotechnology offers to build nanoscale structures with defined chemistries to precisely position biomolecules or drugs for selective cell targeting and drug delivery. Owing to the negatively charged nature of DNA, for delivery purposes, DNA is frequently conjugated with hydrophobic moieties, positively charged polymers/peptides and cell surface receptor-recognizing molecules or antibodies. Here, we designed and assembled cholesterol-modified DNA nanotubes to interact with cancer cells and conjugated them with cytochrome c to induce cancer cell apoptosis. By flow cytometry and confocal microscopy, we observed that DNA nanotubes efficiently bound to the plasma membrane as a function of the number of conjugated cholesterol moieties. The complex was taken up by the cells and localized to the endosomal compartment. Cholesterol-modified DNA nanotubes, but not unmodified ones, increased membrane permeability, caspase activation and cell death. Irreversible inhibition of caspase activity with a caspase inhibitor, however, only partially prevented cell death. Cytochrome c-conjugated DNA nanotubes were also efficiently taken up but did not increase the rate of cell death. These results demonstrate that cholesterol-modified DNA nanotubes induce cancer cell death associated with increased cell membrane permeability and are only partially dependent on caspase activity, consistent with a combined form of apoptotic and necrotic cell death. DNA nanotubes may be further developed as primary cytotoxic agents, or drug delivery vehicles, through cholesterol-mediated cellular membrane interactions and uptake.